Unexpected behavior of Caputo fractional derivative - Kuroda, Lucas Kenjy Bazaglia [UNESP] (2017)
This paper discusses the modeling via mathematical methods based on fractional calculus, using Caputo fractional derivative. From the fractional models associated with harmonic oscillator, logistic equation and Malthusian growth, an unexpected behavior of the Caputo fractional derivative is discussed. The difference between the rate of variation and the order of the Caputo fractional derivative is explained.